Analysis and verification of key technologies for the electrical system of power-concentrated EMUs - LI Peng; ZOU Zhichao (机车电传动)
This paper introduced the research progress and typical applications of power-concentrated EMUs abroad and provided a preliminary comparative analysis of system configurations among various EMU models. It presented overall objectives, technical characteristics, technical challenges, and technical solutions for the development of power-concentrated EMUs, in the context of the technological development and application status of power-concentrated EMUs in China. This paper focused on the analysis and development of key technologies for the design elements of power-concentrated EMUs, including traction, DC 600 V train power supply, and network control systems. Ground tests and field operation show the good performance of the proposed electrical system and its compliance with the requirements of various indicators for electrical systems of power-concentrated EMUs. Its successful development provides solid equipment support for improving the Chinese "Fuxing" EMU family and facilitating the China, s "going out" strategy of high-speed rail systems.